2015
DOI: 10.3389/fimmu.2015.00151
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of IL-17A and TNF-α on Osteoblastic Differentiation of Isolated Synoviocytes and on Bone Explants from Arthritis Patients

Abstract: ObjectiveTNF-α and IL-17A act on fibroblast-like synoviocytes (FLS) and contribute to cytokine production, inflammation, and tissue destruction in rheumatoid arthritis (RA). The aim of this study was to compare their effects on osteogenic differentiation of isolated FLS and on whole bone explants from RA and osteoarthritis (OA) patients.MethodsFibroblast-like synoviocytes and bone explants were cultured in the presence or absence of TNF-α and/or IL-17A. Mineralization of extracellular matrix of FLS was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
2
41
0
1
Order By: Relevance
“…TNF-a (as IL-1) is a key protein implicated in the genesis of osteoarthritis [39,40] and inflammatory synovitis [41]. However, this cytokine is released to the synovial fluid at low concentrations to induce a normal turnover of the cartilage ECM via MMP gene up-regulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a (as IL-1) is a key protein implicated in the genesis of osteoarthritis [39,40] and inflammatory synovitis [41]. However, this cytokine is released to the synovial fluid at low concentrations to induce a normal turnover of the cartilage ECM via MMP gene up-regulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…FN-f treatment has been shown to induce expression of pro-inflammatory cytokines in chondrocytes that include IL-1β, IL-6 and TNF-α 7, 32 that can induce Wnt5a expression 26, 28, 33 , suggesting that FN-f induction of Wnt5a could be mediated by one or more of these factors. However, we observed that Wnt5a expression increased as early as 6 hours after FN-f treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are key players in the initiation of the inflammatory response. As shown in various cells, including endothelial cells or skin and synovial fibroblasts, IL-17 can cooperate with TNF-a to induce in-vitro IL-8 and IL-6 secretion in synergy [16][17][18][19]. As shown in various cells, including endothelial cells or skin and synovial fibroblasts, IL-17 can cooperate with TNF-a to induce in-vitro IL-8 and IL-6 secretion in synergy [16][17][18][19].…”
Section: Introductionmentioning
confidence: 94%